Effects of Expected Future Financial Security and Digital Knowledge on Fintech Behavior - Hesniati Hesniati; Candy -; Edy Marsono; Andhie Febrian; Dimas Zainudin; Jefry - (Universitas Multi Data Palembang, 2026)
The rapid development of financial technology has significantly transformed how individual manage and engage with financial activities. Although fintech enhances financial inclusion and efficiency, its accessibility also introduces challenges, including financial stress, gaps in digital knowledge, and low levels of expected future financial security. In the Indonesian fintech context, this study examines the effects of expected future financial security and digital knowledge on individuals’ financial behavior, while assessing the mediating role of financial stress. The study employs a quantitative research design using a survey method targeting productive-age individuals’ who use fintech services. Data analysis is conducted using Partial Least Squares Structural Equation Modeling to evaluate both direct and indirect relationships among the variables. The findings are expected to contribute theoretically by integrating psychological into financial behavior research, and practically by providing insights for policymakers and fintech providers to develop strategies that improve financial literacy in the digital era.